Academic bullying as a racialized phenomenon in STEM higher education: Centering the experiences of Asian international doctoral students - Wang, Peiwen (Journal of International Students, 2024)
While students of color’s experiences of academic bullying from their advisors have been documented in the literature (e.g., Moss & Mahmoudi, 2021), little is known regarding the role that race plays in the normalization and perpetuation of academic bullying within higher education. Utilizing Asian critical theory (AsianCrit) as both the theoretical and analytical lens, this phenomenological study centers five STEM Asian international doctoral students’ experiences of academic bullying through semi-structured interviews. It is found that racialized academic bullying is operationalized by a) legitimizing exploitation through racializing discourses; b) maintaining White supremacy across transnational contexts; and c) intersecting systems of oppression. Implications and recommendations are offered as to what stakeholders can do collectively to address racialized academic bullying towards minoritized students and to combat systemic inequities and oppression.
Keywords: STEM; dept.cur; peer-reviewed

Planning for Equitable Student Sensemaking: An Examination of Preservice Teachers Noticing of Elementary Science Lesson Plans - Benedict-Chambers, A.; Sherwood, C.-A. (Journal of Science Teacher Education, 2024)
Designing and analyzing lesson plans is a ubiquitous practice in teacher education, and yet we know little about how preservice teachers (PSTs) notice elements of their lesson plans that afford opportunities for supporting equitable student sensemaking. We investigate how the use of a tool, a framework for supporting equitable sensemaking, guided 36 PSTs to notice four features of equitable sensemaking in their plans. Qualitative analysis of PSTs’ comments about their plans generated a coding rubric and three associated levels for noticing. These levels included (1) paying little to no attention to explicit strategies and making assumptions about the ways that traditional classroom practices might facilitate equitable sensemaking; (2) attending to some strategies but providing few details; and (3) attending to and making connections between specific moves and broader principles and practices of supporting equitable student sensemaking. Guided by the tool, PSTs were able to provide elaborate details about their plans to design instruction to engage students in authentic scientific work focused on investigating and explaining phenomenon (feature 4) and to position students as knowers (feature 2), but they struggled to discuss explicit ways to leverage students’ lived experiences in their science lessons (feature 3) and facilitate equitable engagement and participation (feature 1). This suggests that even with the use of a tool, it may be challenging for PSTs to attend to and describe in detail strategies for leveraging students’ out-of-school lives and interests for science learning and explicit classroom strategies for making learning accessible and engaging for all. © 2024 Association for Science Teacher Education.
Keywords: Equitable science instruction; dept.cur; methods courses; noticing; peer-reviewed; preservice teachers